Exploring Subtlety in Charles Mungoshi’s Waiting for the Rain - Jenjekwa, Vincent (2022)
Many critical readers have been contend to characterise Charles Mungoshi’s Waiting for the Rain (1975) as being primarily focused on family relations which seem to be breaking down irrevocably. The argument of this paper is that Waiting for the Rain goes beyond mere exploration of the family relationships of the Mandengu family to be a subtle and calculated attack on the colonial regime in all its manifestations. Mungoshi’s decision to write during a time when the war of liberation in Zimbabwe was in its decisive phase is a decision which called for self censorship. The 1970s, the most painful and brutal years of Zimbabwe’s struggle for independence mark the decisive phase of the liberation war. The settler government had established and consolidated its array of repressive machinery to perpetuate its existence. There was need for subtlety to camouflage political messages from colonial authorities and at the same time ensure that the message of protest reached the intended audience with significant impact. The text will be analysed through Historical Criticism through selected tenets of Psychoanalysis where necessary.